Pediatric obstructive sleep apnea – current concepts in diagnosis and management - Buziak, Jakub; Papińska, Julita; Bojanowski, Szymon; Świderska, Małgorzata; Świstak, Szymon; Powęska, Natalia; Zych, Szymon; Pielacha, Julia (Quality in Sport, 2026)
Background: Pediatric obstructive sleep apnea (OSA) is a common sleep-related breathing disorder causing recurrent upper airway obstruction during sleep and multiple neurocognitive, behavioral, and cardiovascular complications in children. Aim: This review summarizes current evidence regarding the diagnosis and management of pediatric obstructive sleep apnea. Material and methods: A narrative literature review with PRISMA-informed methodology was conducted using PubMed, Scopus, Web of Science, and Google Scholar databases. Literature published between 2016 and 2026 concerning pediatric OSA, polysomnography, adenotonsillectomy, CPAP therapy, and multidisciplinary treatment was analyzed. Results: Pediatric OSA is associated mainly with adenotonsillar hypertrophy, obesity, craniofacial abnormalities, allergic rhinitis, and neuromuscular disorders. Common manifestations include snoring, witnessed apneas, restless sleep, impaired concentration, hyperactivity, and daytime sleepiness. Polysomnography remains the diagnostic gold standard. Adenotonsillectomy is the first-line treatment, while additional therapies include CPAP, anti-inflammatory treatment, orthodontic interventions, weight reduction, and myofunctional therapy. Persistent OSA after surgery remains common in obese and syndromic patients. Conclusions: Pediatric OSA requires early diagnosis and individualized multidisciplinary management. Appropriate treatment may reduce long-term complications and improve quality of life in affected children.